Use of crop sanitation for the management of the banana weevil in Uganda - Masanza, M.; Gold, Cliford S.; Huis, A. van; Ragama, P.E. (2004)
Removal and destruction of banana crop residues after harvest has been widely recommended for the control of banana weevil, cosmopolites sordidus control. However, there is scanty information of the actual effect of this practice on the banana weevil populations and damage. This study aimed at investigating the effect of crop sanitation on the population dynamics of this pest and its associated damage. Laboratory and field studies were conducted in Uganda to study the biology and ecology of this pest on crop residues. We found that corns are the most attractive of all residues parts. Fresh residues were most attractive bot oviposition occured on residues up to 120 days after harvest. An on-farm study of the effect of crop sanitation on populations and corn damage was conducted through farmer paticipatory trials in Ntungamo distrist, Uganda. Increase in sanitation level from low to high significantly reduced banana weevil adult populations, lowered corn damage, increased plant maturation rates and increased yields. The data suggest that improved sanitation management can contribute to C. sordidus control and improved banana productivity.